Effect of Nitrogen and Phosphorus Fertilizers on Seedling Growth and Biomass of Teak (Tectona grandis Linn. F.) on Sodic Soil - Mehta, P.; Rana, B. S.; Verma, S. K. (Indian Forester, 2012)
Nursery raised teak (Tectona grandis) seedlings were given different fertilizer levels of Nitrogen (N), Phosohorus (P) and their combinations to ascertain changes in growth (seedling height and collar diameter) and seedling dry weight. In general, the seedling growth as well as dry weight increased along with increasing doze. Amongst individual application maximum seedling growth and dry weight was indicated at 150 mg level of N. Although, P application also indicated similar pattern, however N application was superior P application. In case of the combined use of N+P fertilizers, growth showed a clear-cut increase along treatments indicating maximum seedling growth (34.6 cm seedling height and 11.48 mm collar diameter) and biomass (65.62 g dry weight seedling) at 100 mg N+75 mg P level). Significant linear relationship (r2 = 7.8 to 8.8; p<0.01) was evident for different parametersunder study.